2008
DOI: 10.1016/j.jelechem.2007.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical dopamine detection: Comparing gold and carbon fiber microelectrodes using background subtracted fast scan cyclic voltammetry

Abstract: Electrochemical detection is becoming increasingly important for the detection of biological species. Most current biological research with electrochemical detection is done with carbon fiber electrodes due to their many beneficial properties. The ability to build electrochemical sensor from noble metals instead of carbon fibers may be beneficial in developing inexpensive multiplexed electrochemical detection schemes. To advance understanding and to test the feasibility of using noble metal electrochemical sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
123
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(129 citation statements)
references
References 37 publications
6
123
0
Order By: Relevance
“…Different kinds of electrodes can be used to sensitively detect DA in the presence of AA and UA. Using FSCV, gold microelectrodes were found to be more sensitive to DA than carbon fiber microelectrodes [35]. In this work, the PPA film thickness can be controlled by the electropolymerization procedure.…”
Section: Interference Studymentioning
confidence: 96%
“…Different kinds of electrodes can be used to sensitively detect DA in the presence of AA and UA. Using FSCV, gold microelectrodes were found to be more sensitive to DA than carbon fiber microelectrodes [35]. In this work, the PPA film thickness can be controlled by the electropolymerization procedure.…”
Section: Interference Studymentioning
confidence: 96%
“…Based on the square-scheme redox mechanism dominated by the adsorption/desorption processes established at classical carbon fiber disk electrodes, [17][18][19] one would expect the current peak intensities of the background corrected CVs, i p corr (v), to vary linearly with the scan rate over the range of scan rates considered in this study. However, the data reported in Figure 5a than that observed in the lower scan rate range (0.28 ± 0.01 nA.s.V −1 , Figure 5b and Table I).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is safely concluded that the oxidation process exclusively involved mechanisms occurring in adsorbed phase as was established at carbon disk microelectrodes. 17,18 A second possible hypothesis which could have explained a drift of i p corr (v) away from linearity in adsorbed films consisted in assuming that at high scan rates the oxidation process was limited by electron-hopping [49][50][51][52][53][54][55] Table I). See text and Table I for the meaning of the other regression lines shown in (b-f).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations